2019
DOI: 10.5210/fm.v24i5.7296
|View full text |Cite
|
Sign up to set email alerts
|

Spanish academics and social networking sites: Use, non-use, and the perceived advantages and drawbacks of Facebook, Twitter, LinkedIn, ResearchGate, and Academia.edu

Abstract: This study examines Spanish academics’ motives for using social networking sites (SNS) and their perceptions regarding the limitations of and drawbacks to social media. We analyse 18 in-depth interviews conducted with Spanish university professors chosen according to their disciplines, academic ranks and level of use. Our findings confirm prior research based on the uses and gratifications theory. Thus, we conclude that SNS are used for managing content, identifying experts in a researcher’s field of knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
(63 reference statements)
0
12
1
Order By: Relevance
“…A survey of 1,639 faculty members from 62 universities in the Association of American Universities list demonstrated that 70% had Facebook accounts (Bowman, ). A qualitative study of professors in Spanish universities found that they used Facebook for personal activities, to create focused research groups, and to connect with students (Segado‐Boj, Díaz‐Campo, Fernández‐Gómez, & Chaparro‐Domínguez, ). Organizations can also use Facebook to share scholarly information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A survey of 1,639 faculty members from 62 universities in the Association of American Universities list demonstrated that 70% had Facebook accounts (Bowman, ). A qualitative study of professors in Spanish universities found that they used Facebook for personal activities, to create focused research groups, and to connect with students (Segado‐Boj, Díaz‐Campo, Fernández‐Gómez, & Chaparro‐Domínguez, ). Organizations can also use Facebook to share scholarly information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, scholars can retain agency. Nonparticipation in the financial market of ideas is a choice that shapes the relationship many have with these platforms, as shown by empirical research on a number of scholarly communities (Jordan and Weller, 2018; Kapidzic, 2020; Segado-Boj et al, 2019). Some may find ways to game these new metrics, as is already common with impact factors and citation counts (Biagioli and Lippman, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Academic social media users take advantage of the diverse objects published on the platform as readers, too. For example, the possibility of 'reading posted conference proceedings, book chapters, and other types of documents not available elsewhere' is cited in studies of scholars' attitudes toward Academia.edu and other social media (Segado-Boj et al, 2019).…”
Section: Economy Of Excessmentioning
confidence: 99%
See 2 more Smart Citations